1986
DOI: 10.1243/pime_proc_1986_200_141_02
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Efficiency of a Cranked Link Chain Drive

Abstract: In a previous paper (I), the contact forces in a chain bearing during articulation were established. The present note describes the application of these results to the theoretical evaluation of efficiency for a conventional chain transmission using cranked link (or offset) type chain. NOTATION energy loss during narrow articulation energy loss during open articulation total energy loss number of teeth in driver sprocket number of teeth in driven sprocket pitch of chain tight span tension bush internal radius b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…M easurement of the tension in a chain link on a quasi-static sprocket [3] showed this model to be reasonably accurate for slow drives with a signi cant slack span or back tension. At approximately the same time, H ollingworth and H ills used a similar force model [4] to formulate equations for the ef ciency of a chain drive by calculating the losses due to sliding friction between the pin, bush and roller during articulation [5]. H owever, the origin of these equations is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…M easurement of the tension in a chain link on a quasi-static sprocket [3] showed this model to be reasonably accurate for slow drives with a signi cant slack span or back tension. At approximately the same time, H ollingworth and H ills used a similar force model [4] to formulate equations for the ef ciency of a chain drive by calculating the losses due to sliding friction between the pin, bush and roller during articulation [5]. H owever, the origin of these equations is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Most publications indicate that the relative motion in the chain joint (articulation) is too complex to be simulated by pin-on-disc or other similar standard wear models and characterization methods [9][10][11][12]. Experiments performed in [9] indicate that wear was observed on most of the pin circumference and that the wear pattern was more equiaxial pitting indicating that the surface has experienced mild fretting in addition to abrasive wear.…”
Section: Wear and Efficiency Modelingmentioning
confidence: 99%
“…If the lubrication, rotational speed, and torque of the transmission are measured to be fixed characteristics of the transmission, and not design parameters, then the transmission efficiency of the transmission is decided principally by selection of the chain and sprocket size. It has been revealed that larger sprockets can increase the transmission efficiency 3–6.…”
Section: Introductionmentioning
confidence: 99%